Use of tetraethylammonium (TEA) and Tris loading for blocking TRPM7 channels in intact cells - Holderby, Katherine G.; Kozak, J. Ashot (Frontiers in Pharmacology, 2024)
Tetraethylammonium (TEA), a quaternary ammonium compound, is a well-known blocker of potassium channels belonging to various subfamilies, such as KV1-3, KCa1, 2 and prokaryotic KcsA. In many cases, TEA acts from the extracellular side by open pore blockade. TEA can also block transient receptor potential (TRP) cation channels, such as TRPM7, in a voltage-dependent manner. In human T lymphocytes, intracellular (cytosolic) TEA and its analog TMA (tetramethylammonium) inhibit TRPM7 channel currents in the outward but not inward direction. By contrast, intracellular Mg2+, protons and polyamines inhibit both outward and inward current components equally. Likewise, the majority of available pharmacological tools inhibit TRPM7 channels in a voltage-independent manner. Since TRPM7 is a steeply outwardly rectifying conductance, voltage-dependent blockers can be useful for studying the cellular functions of this channel. TRPM7 protein is endogenously expressed in diverse cell lines, including HEK, HeLa, CHO, RBL and Jurkat. Using patch-clamp electrophysiology, we found that incubating HEK293 and Jurkat T cells overnight in the presence of 20 mM TEA-Cl, resulted in the nearly complete blockade of whole-cell TRPM7 outward current, measured at break-in. By contrast, the inward current was unchanged in TEA-loaded cells. The blockade was fully reversible after washout of intracellular solution in whole-cell but not in perforated-patch recording configurations. Overnight incubation with 20 mM TMA-Cl resulted in a more modest blockade of the outward TRPM7 current. Internal 129 mM TMA and TEA eliminated most of the outward current. TEA uptake in transfected HEK293 cells led to blockade of recombinant murine TRPM7 and the Mg2+ and pH insensitive Ser1107Arg variant. Unexpectedly, Tris-HCl, a widely used pH buffer, could similarly be loaded into Jurkat and HEK cells, and preferentially blocked outward TRPM7 currents. 20 mM and 129 mM Tris in the internal solution blocked TRPM7 current in outward but not inward direction. Voltage-dependent channel blockade by TEA, TMA and Tris loading will be useful for studying the properties and functions of TRPM7-mediated ion transport in intact cells.